Real-Time Shading Image Implementation Technology for Physical Viod Display - Seo Song, Eun; Tae Kim, Gi; Dae Hong, Sung (International Journal of Engineering and Technology, 2018)
Background/Objectives: The purpose of this study is control technology to reflect user's appearance and movement in the void display in real time.Methods/Statistical analysis: In this paper, we have developed real-time shading image data acquisition based on RGB-D sensor and real-time interaction image control structure for realizing 0-255 Depth image of physical void display. We also study integrated interlocking control solution for integrated interlocking of hardware and software.Findings: Conventional flip displays show data in 0,1 image representation. On the other hand, the void display we are studying acquires real-time data based on RGB-D and shows the data in depth 0-255 image representation.Improvements/Applications: In the void display, the image representation of 0.1 was extended to the depth 0-255 representation.
Keywords: Flip Display; Shading image; physical display; RGB-D sensor; Real-Time Interaction Image Control